1979
DOI: 10.1111/j.1365-2621.1979.tb03796.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Type of Bean, Moisture Level, Blanch Treatment and Storage Time on Quality Attributes and Nutrient Content of Canned Dry Beans

Abstract: The study was conducted on canned dry beans including 8 types, 2 moisture levels, 4 blanching treatments, and 4 storage times. Low original moisture level before soaking resulted in higher hyration ratios in all bean types except Pinks and Avenger. Drained weights were higher in bean types that had lower shear press readings. Beans blanched in steam and lots containing 16% initial moisture were firmer in texture. Blanch method did not affect % splits, but type and storage time created significant differences. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 6 publications
4
25
0
Order By: Relevance
“…In lentil seeds (L. culinaris Medic.) there is no darkening at 5 C (Nordstorm & Sistrunk, 1979) and it is slow in adzuki beans (Vigna angularis) at 10 C (Yousif et al, 2003). So similar to other legumes, storage at 5 C best protected faba bean postharvest colour during long term storage.…”
Section: Effect Of Storage Temperature and Duration On The Stability mentioning
confidence: 95%
See 1 more Smart Citation
“…In lentil seeds (L. culinaris Medic.) there is no darkening at 5 C (Nordstorm & Sistrunk, 1979) and it is slow in adzuki beans (Vigna angularis) at 10 C (Yousif et al, 2003). So similar to other legumes, storage at 5 C best protected faba bean postharvest colour during long term storage.…”
Section: Effect Of Storage Temperature and Duration On The Stability mentioning
confidence: 95%
“…Lentil (Lens culinaris Medic.) seeds exposed to moderately high temperature (20 and 30 C) at high RH (100%) turned brown in 3 weeks or less while at cool temperature (5 C) with same RH (100%) browning did not occur before 5 weeks (Nordstorm & Sistrunk, 1979;Nozzolillo & De Bezada, 1984). Similarly little change in postharvest seed coat colour occurred in Rwandan dry beans (P. vulgaris) stored at 4 C for 24 months (Edmister, Breene, & Serugendo, 1990).…”
Section: Introductionmentioning
confidence: 95%
“…A cracked seed coat is a permanent damage resulting in an inferior canned product. Beans with moisture content above 13% deteriorate significantly in texture and flavor after 6 months at 25°C (32). Inhibition of these changes is important in the development of an optimum storage environment, temperature, atmosphere, and equilibrium moisture content (a w ) for the freshly processed product (29).…”
Section: Changes During Storagementioning
confidence: 99%
“…Bean culinary quality depends on seed attributes at harvest and handling, storage conditions, and processing procedures over which controls are exerted (18). Differences in cultivar with the subsequent differences in chemical composition also affect the ultimate quality of canned beans (32). Beans not meeting culinary quality expectations may be unacceptable for human consumption.…”
Section: Canned Beansmentioning
confidence: 99%
“…Previous studies indicated that a large portion of the folates in edible beans are lost during canning processes (Dang, Arcot, & Shrestha, 2000;Deleon, Elias, & Bressani, 1992;Nordstorm & Sistrunk, 1979). The water solubility and oxygen and heat susceptibility of folates leads to massive loss of this vitamin from vegetables during process and storage (Pietrizik, 1984).…”
Section: Introductionmentioning
confidence: 99%